2019
DOI: 10.1001/jamaneurol.2019.1305
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Presentation and Outcome After an Acute Transient or Minor Neurologic Event

Abstract: ; for the SpecTRA Study Group IMPORTANCE Sex differences have been described in the presentation, care, and outcomes among people with acute ischemic strokes, but these differences are less understood for minor ischemic cerebrovascular events. The present study hypothesized that, compared with men, women are more likely to report nonfocal symptoms and to receive a stroke mimic diagnosis. OBJECTIVE To evaluate sex differences in the symptoms, diagnoses, and outcomes of patients with acute transient or minor neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 34 publications
4
61
0
Order By: Relevance
“… 27 However, in our study the proportion of migraine was similar in both sexes, the rate of atypical TIA was lower than previously described, 15 and no significant differences between sexes were observed for late SR. To the best of our knowledge, this is the first time that differences between sexes have been analyzed in a cohort of consecutive patients with TIA in long-term follow-up. Previous studies of differences between sexes in outcomes after TIA or minor strokes reported the same risk of SR after 30 days, 28 90 days, 4 and 1 year 28 of follow-up. In our study, LAA was the main predictor of SR in both sexes, with the risk of SR falling after the first five years of follow-up.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… 27 However, in our study the proportion of migraine was similar in both sexes, the rate of atypical TIA was lower than previously described, 15 and no significant differences between sexes were observed for late SR. To the best of our knowledge, this is the first time that differences between sexes have been analyzed in a cohort of consecutive patients with TIA in long-term follow-up. Previous studies of differences between sexes in outcomes after TIA or minor strokes reported the same risk of SR after 30 days, 28 90 days, 4 and 1 year 28 of follow-up. In our study, LAA was the main predictor of SR in both sexes, with the risk of SR falling after the first five years of follow-up.…”
Section: Discussionmentioning
confidence: 87%
“… 2 , 3 Even so, only limited data are available about differences in sex relating to its clinical presentation, cause, imaging features, and prognosis after a transient ischemic attack (TIA). Yu et al 4 recently observed a similar risk of subsequent vascular events between sexes in a prospective cohort of patients with minor stroke. The early risk of stroke after a TIA is high 5 , 6 and urgent management is required 7 ; however, few studies have focused on the long-term risk of stroke after TIA.…”
mentioning
confidence: 78%
“…Furthermore, women with stroke often present with non-traditional symptoms like altered mental status 28 , which could be overlooked or misdiagnosed in the clinical setting. 29,30 Sex differences in clinical presentations are also present in dementia 31 but none of the included studies reported these in VaCI or VaD. Moreover, informal carers of dependent persons in the UK are more likely to be middle-aged women with multiple roles until later life (70+).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are known to be significant differences between men and women in relation to symptom reporting, with women reporting more intense, more numerous and more frequent symptoms compared to men (Barsky et al 2001). Despite this generally increased symptom reporting, however, research has also demonstrated that women may be less likely to receive diagnoses, as has been shown in the case of stroke, for instance (Yu et al 2019). In the current study, we controlled for doctor-diagnosed conditions as part of a mediation analysis to see if health might explain associations between loneliness and increased HCU, but if women were less likely to receive these diagnoses, this could have impacted our results.…”
Section: Loneliness and Healthcare Usementioning
confidence: 94%